1999
DOI: 10.1116/1.590810
|View full text |Cite
|
Sign up to set email alerts
|

GaP(001) and InP(001): Reflectance anisotropy and surface geometry

Abstract: We have investigated the optical anisotropy of GaP͑001͒ and InP͑001͒ surfaces. The samples were prepared by homoepitaxial metalorganic vapor phase epitaxy growth and either directly transferred into ultrahigh vacuum ͑UHV͒ or in situ capped and, after transfer, decapped in UHV by thermal desorption of a P/As capping layer. Symmetry, composition, and surface optical anisotropy were characterized by low-energy electron diffraction, Auger electron spectroscopy, and reflectance anisotropy spectroscopy. We observe (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
28
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…1) has been generally established [4,5]. For the much-studied case of GaAs, the extensive experimental and theoretical knowledge accumulated about the surface structure has led to significant progress in understanding the atomistic mechanisms of growth during molecular beam epitaxy (MBE) [6,7].…”
mentioning
confidence: 99%
“…1) has been generally established [4,5]. For the much-studied case of GaAs, the extensive experimental and theoretical knowledge accumulated about the surface structure has led to significant progress in understanding the atomistic mechanisms of growth during molecular beam epitaxy (MBE) [6,7].…”
mentioning
confidence: 99%
“…(4 Â 2) reconstructions with Ga or P dimers in the uppermost atomic layer are unstable. The comparison of measured and calculated reflectance anisotropy spectra support the mixed-dimer reconstruction of the Ga-rich GaP(001) surface [8,9]. This has recently been confirmed by a comparison of calculated and measured scanning-tunneling microscopy (STM) images [10].…”
Section: Introductionmentioning
confidence: 49%
“…A slightly different behaviour is found for samples grown by metal-organic vapour phase epitaxy or chemical beam epitaxy as well as for GaP(001) surfaces prepared by thermal desorption of a protective arsenic/phosphorous double layer cap under ultrahigh vacuum conditions [7][8][9]. After annealing to 690 K the de-capped GaP(001) surfaces show a (2 Â 1)=(2 Â 2)-like LEED pattern.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…11 Applying in situ reflection anisotropy spectroscopy (RAS), we recently showed that the formation of the interface between GaP(100) and water depends highly on the atomic structure of the GaP surface prior to exposure. 12 RA spectra of P-rich and Ga-rich GaP(100) surfaces are well-understood both in theory 13,14 and experiment, [15][16][17] which enables precise in situ control during MOVPE preparation. Pseudomorphic GaP/Si(100) surfaces can be prepared analogously to GaP(100) regarding atomic order.…”
mentioning
confidence: 99%